2001
DOI: 10.1161/hy1001.096212
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Pressure Changes With Six Classes of Antihypertensive Agents in a Randomized, Controlled Trial

Abstract: Abstract-Pulse pressure has been more strongly associated with cardiovascular outcomes, especially myocardial infarction and heart failure, than has systolic, diastolic, or mean arterial pressure in a variety of populations. Little is known, however, of the comparative effects of various classes of antihypertensive agents on pulse pressure. In retrospective analyses of the Veterans Affairs Single-Drug Therapy for Hypertension Study, we compared changes in pulse pressure with 6 classes of antihypertensive agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 31 publications
(27 reference statements)
2
25
0
4
Order By: Relevance
“…This approach assumes that medicated individuals had a minimum PP of 55 mm Hg at the time of treatment onset. This fixed value compares well with that from other studies 35,9 (53 and 62 mm Hg, respectively). In our population, 55 mm Hg corresponds to 1 SD above the population mean for unmedicated individuals after correction for sex, age, age 2 , and body mass index (Table 1).…”
Section: Statistical Analysessupporting
confidence: 89%
“…This approach assumes that medicated individuals had a minimum PP of 55 mm Hg at the time of treatment onset. This fixed value compares well with that from other studies 35,9 (53 and 62 mm Hg, respectively). In our population, 55 mm Hg corresponds to 1 SD above the population mean for unmedicated individuals after correction for sex, age, age 2 , and body mass index (Table 1).…”
Section: Statistical Analysessupporting
confidence: 89%
“…20 In small clinical studies, use of angiotensin-converting enzyme inhibitors (␤-blockers), diuretics, and clonidine have been associated with modest reductions in arterial stiffness. [33][34][35] Statin use has also been associated with reduced arterial stiffness independent of reductions in cholesterol in patients with hypercholesterolemia. 36 None of these agents are designed to specifically modify arterial composition.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,7 Among non-selective alpha-1 antagonists used for the treatment of BPH, terazosin hydrochloride (terazosin), prazosin hydrochloride, and urapidil have also been employed for the treatment of hypertension. [8][9][10] Our previous study showed that elderly patients with nocturia had a higher blood pressure and higher serum catecholamine levels when compared with healthy elderly controls. 11 Therefore, hypertension itself seems to have an adverse influence on lower urinary tract symptoms (LUTS).…”
Section: Introductionmentioning
confidence: 99%